Erp1/Emi2 is essential for the meiosis I to meiosis II transition in Xenopus oocytes - Ohe, Munemichi; Inoue, Daigo (Developmental biology, 2006)
Erp1 (also called Emi2), an inhibitor of the APC/C ubiquitin ligase, is a key component of cytostatic factor (CSF) responsible for Meta-II arrest in vertebrate eggs. Reportedly, however, Erp1 is expressed even during meiosis I in Xenopus oocytes. If so, it is a puzzle why normally maturing oocytes cannot arrest at Meta-I. Here, we show that actually Erp1 synthesis begins only around the end of meiosis I in Xenopus oocytes, and that specific inhibition of Erp1 synthesis by morpholino oligos prevents entry into meiosis II. Furthermore, we demonstrate that premature, ectopic expression of Erp1 at physiological Meta-II levels can arrest maturing oocytes at Meta-I. Thus, our results show the essential role for Erp1 in the meiosis I/meiosis II transition in Xenopus oocytes and can explain why normally maturing oocytes cannot arrest at Meta-I.